Des ATSEM « maternelles » aux « animatrices ». Transformation de l’identité professionnelle des travailleuses éducatives subordonnées de l’école maternelle - Arthur Imbert (Recherches en Éducation)
Over the past thirty years or so, ATSEM (agentes territoriales spécialisées des écoles maternelles) have crossed the threshold of the classroom to assist teachers in their pedagogical missions. This article, based on interview and statistics datas, looks at the consequences of this development in terms of the contours of the professional group and, in particular, professional identity. Two main identities emerge: the « maternals » and the « animators ». The former, more experienced and more popular, defend a vision of their profession on the margins of the classroom, focused on ensuring the well-being of pupils. The latter, younger in the profession and with multiple subordinate professional experiences in the socio-educational field, focus their activity on pedagogical work. Using the case of ATSEMs, we explore the consequences of the increasing complexity of the division of educational work over the last fifty years.